A framework for helping teachers interrupt oppression in their classrooms. Issue 1 (8th April 2019) - Muller, Meir; Boutte, Gloria S.
Abstract : Purpose: Providing insights into the need to go beyond superficial equity efforts in classrooms, the authors present a standardized test analogy to make the concept of oppression accessible and relevant for educators. Three levels of oppression (individual, institutional and cultural/societal) are described along with a brief overview of Paulo Freire's four dimensions of oppression. Drawing parallels from a children's book, Testing Miss Malarkey (Finchler, 2014), strategies for recognizing and interrupting oppression are offered. The authors recommend resources that teachers can use to help children and themselves take reflective actions (praxis) to interrupt systemic types of oppressions in their classrooms and personal spaces. Design/methodology/approach: This paper is grounded in the belief that to teach in socially just and equitable ways, educators benefit from a fundamental understanding of how systems of oppression work in classrooms and in society. The paper provides both a theoretical and practical approach to help guide educators' efforts in such a way as to address systemic issues of racism, classism, sexism, heterosexism and other "isms" (systems of oppression). Findings: This paper does not present findings such as those found in an empirical study. However, it does provide an overview of Freire's levels of oppression along with instructional guidelines to assist teachers in helping provide children with tools to understand oppression and to take reflective actions (praxis) to make a dent in systemic types of oppressions in their classrooms and worldwide. Research limitations/implications: There are many other decolonizing frameworks that are available. This translational study focuses on one of them (Freire') and what it means for teachers. Practical implications: Believing that the school years are foundational for providing children with the tools that they need to be able to identify and address the ongoing acts of oppression, this paper seeks to make the topic accessible to educators with the hope that they can make a lasting and positive difference in children's lives (and in society in general). Recommended resources are provided. Social implications: To interrupt and counter oppression, educators must be informed. The benefits of doing so readily extend to society in general; so, it is important for both educators and students to understand oppression and have tools for disrupting it. Originality/value: This paper takes the original approach of using standardized tests as analogy to make the concept of oppression accessible and relevant for educators. The authors use this example because they recognize that many teachers can identify with feeling disempowered by the standardized testing mandates and frenzy. They believe that educators will be able to extrapolate the process by which the loss of their power occurs with standardized testing to understand how institutional oppression works. Neither author has seen an article that uses an analogy from the professional lives of teachers to illustrate oppression.